2015
DOI: 10.1007/s00500-015-1712-7
|View full text |Cite
|
Sign up to set email alerts
|

Picture fuzzy clustering: a new computational intelligence method

Abstract: Fuzzy clustering especially fuzzy C-means (FCM) is considered as a useful tool in the processes of pattern recognition and knowledge discovery from a database; thus being applied to various crucial, socioeconomic applications. Nevertheless, the clustering quality of FCM is not high since this algorithm is deployed on the basis of the traditional fuzzy sets, which have some limitations in the membership representation, the determination of hesitancy and the vagueness of prototype parameters. Various improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 33 publications
0
56
0
4
Order By: Relevance
“…Le Hoang Son et al in [11,13,14] has shown that " Picture Fuzzy Sets Theory" is a new approach to many Computational Intelligence problems . This paper reviewed some recent researches about soft computing methods on picture fuzzy sets.…”
Section: Problem 3 Applications To Computational Intelligence Problemsmentioning
confidence: 99%
“…Le Hoang Son et al in [11,13,14] has shown that " Picture Fuzzy Sets Theory" is a new approach to many Computational Intelligence problems . This paper reviewed some recent researches about soft computing methods on picture fuzzy sets.…”
Section: Problem 3 Applications To Computational Intelligence Problemsmentioning
confidence: 99%
“…By replacing traditional fuzzy sets with intuitionistic fuzzy set, Chaira introduced the intuitionistic fuzzy clustering (IFC) method in [8], which integrated the intuitionistic fuzzy entropy with the objective function. Hwang and Rhee suggested deploying FCM on (interval) Type-2 fuzzy set sets in [9], which aimed to design and manage uncertainty for fuzzifier m. Thong and Son proposed picture fuzzy clustering based on the picture fuzzy set (PFS) in [10]. Second, the kernel-based method is applied to improve the fuzzy clustering quality.…”
Section: Introductionmentioning
confidence: 99%
“…Thong and Son did significant work on clustering based on PFS. In [10], a picture fuzzy clustering algorithm, called FC-PFS, was proposed. In order to determine the number of clusters, they built an automatically determined most suitable number of clusters based on particle swarm optimization and picture composite cardinality for a dataset [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the fuzzy set, several additional and hybrid concepts such as theintervalvalued fuzzy set [69], the type-2 fuzzy set [69], the intuitionistic fuzzy set [2] were developed. Fuzzy sets play a tremendous role in signal processing [25], control theory [14], reasoning [7], decision making [23], medical diagnosis [31], geo-demographic analysis [33,37,41,42,65], dental segmentation [47,48,59], compression [43], recommender systems [34,36,38] and other fields [8,10,35,39,40,46,49,50,[56][57][58].…”
Section: Introductionmentioning
confidence: 99%